A new species of Coriella, Coriella chernyshevi n. sp. (Entoprocta, Barentsiidae), with comments on the genera Coriella and Pedicellinopsis - Borisanova, Anastasia O.; Potanina, Darya M. (Zootaxa, 2016)
Here we describe a new species of colonial entoproct Coriella chernyshevi n. sp. from the Sea of Okhotsk, western Pacific Ocean, found at depths of 305–624 m. This is the first record of an entoproct species for the Sea of Okhotsk. Coriella chernyshevi is a large species with a zooid length of 6–7 mm. The calyx bears 32–34 tentacles. Zooids extend from a central stem formed by closely adjoined stolons. Only one other species of Coriella has been described previously, Coriella stolonata Kluge, 1946, from the Arctic Ocean, found at a depth of 45 m. Coriella chernyshevi and C. stolonata share a same rigid stem structure, but they differ in zooid size and tentacle number. The only other barentsiid that has been described as having a rigid central stem is Pedicellinopsis fruticosa Hincks, 1884. Based on the presence of a central stem in colonies, and similarities in structure of zooids and colonies, we suggest a close relationship between Coriella and Pedicellinopsis. Finally, an overview of both genera and all three species is given.